2018
DOI: 10.1038/s41598-018-23556-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Oxidation Behaviour of Ti and Al in Inconel 718 Superalloy During Electroslag Remelting

Abstract: In the current study, the thermodynamics of the slag-metal equilibrium reaction between Inconel 718 Ni-based alloy and CaF2-CaO-Al2O3-MgO-TiO2 electroslag remelting (ESR)-type slags were systematically investigated in the temperature range from 1773 to 1973 K (1500 to 1700 °C). The equilibrium Al content increased with increasing temperature, whereas the equilibrium Ti content decreased with increasing temperature at a fixed slag composition. The important factors for controlling the oxidation of Al and Ti in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Also, the high affinity of Ti and V for N lead to the formation of (TiV)N inclusions. The presence of TiO 2 at the high temperatures in the slag (1700-2000 o C) [33] and the addition of Al metal allow the reduction of TiO 2 through an exothermic aluminothermic reduction reaction [34,35] as in equation (4). Subsequently, once the Ti reaches the molten metal pool, TiN, (TiV)N, and TiO 2 are formed thereby explaining the presence of these types of inclusions in the ESR material while they are absent from the IF material.…”
Section: Chemical Composition Of Nmismentioning
confidence: 99%
“…Also, the high affinity of Ti and V for N lead to the formation of (TiV)N inclusions. The presence of TiO 2 at the high temperatures in the slag (1700-2000 o C) [33] and the addition of Al metal allow the reduction of TiO 2 through an exothermic aluminothermic reduction reaction [34,35] as in equation (4). Subsequently, once the Ti reaches the molten metal pool, TiN, (TiV)N, and TiO 2 are formed thereby explaining the presence of these types of inclusions in the ESR material while they are absent from the IF material.…”
Section: Chemical Composition Of Nmismentioning
confidence: 99%
“…While in the equilibrium reaction experiments using the 2#~4# slags, the loss of the equilibrium content of Si and the increasement of the equilibrium content of Al was slight, and the equilibrium B, Si, and Al contents kept steady soon. The redox reactions between the molten slag and steel were in quasi-equilibrium state, thus the proper slag for ESR remelting 9CrMoCoB ingot were the 2#, 3#, and 4# slags [10,19].…”
Section: Results Of Equilibrium Reaction Experimentsmentioning
confidence: 99%
“…To reduce the loss of main reinforced element B and the accumulation of deleterious element Al, SiO 2 and B 2 O 3 should be added into the slag to decrease the degree of slag-metal reactions [19]. To study the effects of B 2 O 3 and SiO 2 addition into the molten slag on the B, Si, and Al contents in the steel, the compositions of the basic slag of CaF 2 -CaO-Al 2 O 3 -MgO should be determined first.…”
Section: Experiments and Calculationsmentioning
confidence: 99%
“…Our data have shown that the application of ZrO 2 in both shapes did not affect chemical composition of implant but add some additional oxygen, which is probably due to the incorporation of ZrO 2 . Chemical interaction of the metal with the abrasive, a strong adherence of particles to the surface layer, and additional surface oxidation are observed in the surface layers that are activated in such a way [23,32].…”
Section: Discussionmentioning
confidence: 99%